Ocular changes over 60 min in supine and prone postures - Anderson, Allison P. (J Appl Physiol (1985), 2017)
Some astronauts are returning from long-duration spaceflight with structural ocular and visual changes. We investigated both the transient and sustained effects of changes in the direction of the gravity vector acting on the eye using changes in body posture. Intraocular pressure (IOP; measured by Perkins tonometer), ocular geometry (axial length, corneal thickness, and aqueous depth-noncontact biometer), and the choroid (volume and subfoveal thickness optical coherence tomography) were measured in 10 subjects (5 males and 5 females). Measures were taken over the course of 60 min and analyzed with repeated-measures analysis of covariance to assess the effects of posture and time. In the supine position, choroidal volume increased significantly with time (average value at <5 min = 8.8 ± 2.3 mm(3), 60 min = 9.0 ± 2.4 mm(3), P = 0.03). In the prone position, IOP and axial length increased with time (IOP at <5 min 15 ± 2.7 mmHg, 60 min = 19.8 ± 4.1 mmHg, P < 0.0001; axial length at <5 min = 24.29 ± 0.77 mm, 60 min = 24.31 ± 0.76 mm, P = 0.002). Each increased exponentially, with time constants of 5.3 and 14 min, respectively. Prone corneal thickness also increased with time (<5 min = 528 ± 35 μm, 60 min = 537 ± 35 μm(3), P < 0.001). Aqueous depth was shortened in the prone position (baseline = 3.22 ± 0.31 mm, 60 min = 3.18 ± 0.32 mm, P < 0.0001) but did not change with time. The data show that changes in the gravity vector have pronounced transient and sustained effects on the geometry and physiology of the eye. NEW & NOTEWORTHY We show that gravity has pronounced transient and sustained effects on the eye by making detailed ocular measurements over 60 min in the supine and prone postures. These data inform our understanding of how gravitational forces can affect ocular structures, which is essential for hypothesizing how ocular changes could occur with microgravity exposure.